PERAN NOTARIS DARI PERSPEKTIF HUKUM DALAM PROSES PEMBUATAN AKTA AKUISISI PERUSAHAAN TERBUKA - Mohammad Adrian (Media Bina Ilmiah, 2025)
One of the roles of a Notary in the Capital Market concerns the takeover of shares in a private limited company. However, acquisitions of companies does not only involve private companies but also can be carried out against public companies. In general, acquisitions are regulated in the Company Law, but specifically for Public Companies, acquisitions are regulated in Financial Services Authority Regulation (OJK) Number 9/POJK.04/2018 concerning Acquisitions of Public Companies. The research method used in this research is a normative legal research type, the research typology used is prescriptive research whose aim is to determine the role that a Notary can play in making a deed of acquisition of a Public Company. The type of data used is primary and secondary data, the data analysis method used is a qualitative method using data collection procedures for studying documents or library materials. The role of the Notary was found to be related to providing legal counseling before, during and after the Deed of Acquisition was made. Apart from that, the Notary's role is to make deeds related to the acqusitions, but in practice it is found that acqusitions in public companies are not always made in a separate deed. As a result, the acquisition deed is not in accordance with the Financial Services Authority Regulations. In relation to a Notary who carries out activities in the Capital Market, the Notary may be subject to the Notary's responsibility for civil and administrative sanctions for errors made. Even though administrative sanctions are applied, this does not eliminate responsibility for criminal sanctions if these elements are met. Regarding the acquisition deed, if the deed is not made in accordance with Financial Services Authority Regulation (OJK) 67/POJK.04/2017 then the deed is actually still valid as a deed but no longer has legal force as a result of the cancellation of the deed.